Organizational Barriers of a Knowledge-Based Organization in the Aspect of Sustainable Creativity Development - Martina Blašková; Aneta Sokół; Irena Figurska (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The turbulence of the organizations’ environment significantly affects the functioning of creative knowledge-based organizations. Changes that occur in this broadly understood environment are often unpredictable, so it is impossible to prepare for them. Therefore organizations must creatively use their knowledge in their response to these changes. Bearing the above in mind, the issue of organizational barriers of sustainable creativity development in knowledge based organizations seemed to be worth the research effort. The paper analyses, synthesizes and compares the theory (regarding the essence of a knowledge-based organization, the sustainable development of creativity in organizations and the barriers that hinder this development), processes empirical data, verifies hypotheses, and provides conclusions and suggestions for knowledge based organizations (both those taking up and not taking creative activities) regarding the minimization of barriers affecting the sustainable development of creativity. The empirical analysis uses the Spearman correlation coefficient, Chi-square test, Mann-Whitney test, W Wilcoxon’s test and simple rotation factor analysis. The results of the research showed significant differences in the following barriers of sustainable creativity development: lack of knowledge on the organization’s vision, goals and plans, poor financial condition of the organization, and fear to present own ideas. Subsequently, with use of appropriate statistical apparatus, the 28 primarily defined barriers were turned out to into the six heterogeneous category – groups of the barriers limiting the sustainable development of creativity in knowledge-based organizations. The results of the study made it possible to identify areas the improvement of those may allow for more effective development of the organization in the scope presented in the paper. The article ends with recommendations that respond to the barriers with the strongest negative impact on the sustainable creativity development.